Pelatihan kewirausahaan untuk menjaga mutu mie kering ebi dengan berbagai kemasan dan pelabelan di Kabupaten Takalar - Diyahwati Diyahwati; Amirah Mustarin; Muhammad Wiharto (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Dried prawn noodles is one of the foods that isfavored by Indonesian people since the taste is crunchy andtasty, healthy, and it can be used as a souvenir. Dried prawnnoodles have a long shelf life, but they are hygroscopic so theyare easily damaged and the additional protection is needed.Most of home industries, including dried prawn noodlesindustries in the Sandrobone District, Takalar, generally do notconduct a good way of packing. Thus, the noodles are easilydamaged and lose its taste. The aim of implementing theCommunity Partnership Program in packaging and labeling ofdried prawn noodles was to improve the knowledge and skillsof participants in the Sanrobone District of Takalar Regency.The activities included: (1) Implementation of the CommunityPartnership Program in the Sanrobone District on packagingand labeling training of dried prawn noodles was an effectiveand efficient way to introduce dried prawn noodle products,especially for the new entrepreneurs; (2) This training as partof the Community Partnership Program was not onlyincreasing participants’ knowledge, but also could improve theskills of participants in choosing the type of packaging thatwas suitable for dried prawn noodles and the participants ableto make their own product labels; (3) This packaging andlabeling training of dried prawn noodles was supported by thepeople in the Sanrobone District. It was evidenced by theratings obtained from questionnaires. The average score was3.49 or categorized as good.